Metrical Verse as a Rule of Qurâanic Translation: Some Reflections on R.A.A. Wiranatakoesoemahâs Soerat Al-Baqarah (1888â1965) - Rohmana, Jajang A (Al-Jamiah Research Centre, 2015)
The paper aims to analyze how literary translations of the Quran can grasp the meaning of the Quran and âsubordinateâ it to local poetry rules, using R.A.A. Wiranatakoesoemaâs Soerat Al-Baqarah as the object of study. It is a Sundanese poetic translation of the Quran in the form of guguritan or dangding and as such this study is focused on the implications of canto rules to the Quranic meaning field in the translation, analyzed using intertextual studies and semantic analysis. This research shows that the use of guguritan in the translation of the Quran might cause a problem of inaccessibility of the translated meaning. There are some implications of subordination of the translation of the Quran following the rules of guguritan. This tradition affected the expansion or constriction of the meaning, which in turn caused modification within the verses (ayat) in translation, and forced the use of loan words, particularly Malay. This study is significant not merely for demonstrating a diglossic ideology on language of the Quran that has affected Sundanese literature, but also for strengthening the thesis that âSundanizationâ of the Quran was performed as a form of resistance against Islam and Arabness through cultural impulsesâespecially Sundanese literature. Wiranatakoesoemaâs Soerat Al-Baqarah is a creative effort that should be appreciated, but it must be noted that literary language can never be completely satisfactorily compared and translated.[Tulisan ini menjelaskan bagaimana penerjemahan al-Quran dapat mencapai makna seutuhnya dengan âmenurunkanâ standarnya sesuai aturan susastra lokal, yang tersirat pada pengkajian Soerat Al-Baqarah karya R.A.A Wiranatakoesoema. Terjemahan surat ini merupakan alih bahasa dalam bentuk susastra Sunda yang disebut dengan guguritan atau dangding. Tulisan ini berfokus pada implikasi aturan pupuh pada medan makna penerjemahan al-Quran dengan menggunakan analisis intertekstual dan semantik. Dalam kajian ini menunjukkan bahwa penggunaan guguritan dalam penerjemahan al-Quran dapat menyebabkan persoalan ketidaksampaian makna terjemahan. Terdapat beberapa implikasi antara lain âsubordinasiâ pada terjemahan. Hal ini disebabkan oleh perluasan atau penyempitan makna akibat modifikasi dalam penerjemahan ayat dan pemaksaan dalam peminjaman kata, khususnya Melayu. Kajian ini penting karena tidak hanya menunjukkan konsep diglosia dalam terjemahan al-Quran akibat pengaruh bahasa Sunda, tetapi juga menguatkan pendapat bahwa âSundanisasiâ merupakan usaha resistensi terhadap Islam dan Arab melalui susastra Sunda. Karya Wiranatakoesoema layak untuk diapresiasi sebagai usaha kreatif, meskipun perlu dicatat bahwa bahasa susastra tak akan cukup memuaskan untuk dibandingkan atau diterjemahkan.â]